Amazon River water in the northeastern Caribbean Sea and its effect on larval reef fish assemblages during April 2009. (11th November 2014) - Johns, E. M.; Muhling, B. A.; Perez, R. C.; Müller‐Karger, F. E.; Melo, N.; Smith, R. H.; Lamkin, J. T.; Gerard, T. L.; Malca, E.
Abstract During April to June 2009, a large bolus of Amazon River water impacted the northeastern Caribbean Sea. Shipboard observations collected near Saba Bank, the U.S. and British Virgin Islands, and the Anegada Passage showed low surface salinity (35.76 ± 0.05 Practical Salinity Unit (PSU)), elevated surface temperature (26.77 ± 0.14°C), high chlorophyll‐a (1.26 ± 0.21 mg m−3) and high dissolved oxygen (4.90 ± 0.06 mL L−1) in a 20‐ to 30‐m thick surface layer in the riverine plume. The water was ~1°C warmer, 1 PSU fresher, 0.3 mL L−1 higher in oxygen and 1.2 mg m−3 higher in chlorophyll‐a than Atlantic Ocean waters to the north, with Caribbean surface waters showing intermediate values. Plankton net tows obtained in the upper 100 m of the water column revealed larval fish assemblages within the plume that were significantly different from those of the surrounding waters and from those encountered in the area in previous years. The plume waters contained higher concentrations of mesopelagic fish larvae from the families Myctophidae and Nomeidae, which as adults typically inhabit offshore, deep water habitats. Concentrations of larvae from inshore and reef‐associated families such as Scaridae, Serranidae, Labridae and Clupeidae were lower than those found outside the plume in similar shallow areas, particularly in near‐surface waters. An event like the one observed in 2009 had not been documented in at least the past 30 yr, and yet it was followed by another similarly extreme event in 2010. The ecological implications, including any long‐term consequences of such recent extreme events, are important and merit further study.